IMPLEMENTASI PENDIDIKAN LIFESKILL SEJAK DINI DALAM PEMBELAJARAN ENTERPRENEURSHIP - Yeni Suprihatin; Etika Lisyana Dewi (Jurusan PGMI FTIK IAIN Metro Lampung, 2018)
Life skill education is an education that provides basic supplies and training to learners about the values of life needed and useful for the development of everyday life. Research on integrated life skill education in enterpreneurship subject in SMP Cahaya Bangsa School aims to know what life skill orientation in Entrepreneurship subject and examine the extent of life skill education implementation in Enterpreneurship subject. The design of this study used qualitative research with case study type. A descriptive inductive approach is used to describe a case by understanding symptoms and meaning. Researchers use in-depth interview techniques, digging information with direct observation, and study documentation. In analyzing the data, the researcher through three main components, namely, data reduction, display data, and data conclusion drawing. The results showed that the concept of life skill education is internalized in the entrepreneurship subject syllabus, then the teacher describes it in various learning activities such as washing activities, ironing activities, live in program, and market day. Evaluation done by teacher in assessing ability of life skill of student is by observing directly activity in enterpreneurship subject and student also given duty to write report result of activity live in.